PA2146 Gene Knockout Is Associated With Pseudomonas aeruginosa Pathogenicity in Macrophage and Host Immune Response - She, Pengfei; Liu, Yiqing; Luo, Zhen; Chen, Lihua; Zhou, Linying; Hussain, Zubair; Wu, Yong (Frontiers in Cellular and Infection Microbiology, 2020)
Pseudomonas aeruginosa is a common gram-negative pathogen that often causes nosocomial infection. The main pathogenicity of P. aeruginosa is caused by its virulence factors. PA2146 is recognised to be a potential virulence-regulating gene and is highly expressed in the biofilms of P. aeruginosa; however, no studies have reported the effects of PA2146 mutant (PAO1ΔPA2146) on macrophage immune response and murine models. In the present study, PA2146 knockout was performed by homologous recombination. We found that PAO1ΔPA2146 stimulation strongly increased pyocyanin production but inhibited interleukin-6 secretion by neutrophils compared to PAO1 stimulation. In addition, PAO1ΔPA2146 treatment significantly inhibited cytokine production in macrophages independent of cell killing. In an acute pneumonia murine infection model, treatment with P. aeruginosa infected with PAO1ΔPA2146 inhibited cytokine secretion in the lungs but enhanced inflammatory cell infiltration compared to the wild-type group. The paradoxical results indicate that PA2146 deletion may also increase the production of virulence factors other than pyocyanin, which might not only increase inflammatory cell infiltration in the lungs but also cause immune cell ‘shock’. Overall, our findings suggest that PA2146 could serve as a P. aeruginosa virulence-regulating gene that regulates its macrophage and host immune response.